(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In this article, the introduction of the law “On the state language” and the law “On the introduction of the Uzbek alphabet based on the Latin alphabet” represents the history of the creation of the law, as well as the development based on the basic principle “From national revival to national uplift” is mentioned in the update.